Diagnosis of Congenital Anomalies of Kidney and Ureter by Ultrasonography (Journal of Paediatric Surgeons of Bangladesh, 2015)
Present study was conducted to investigate the diagnostic accuracy of transabdominal ultrasonography in correlation with IVU in suspected patients of Congenital anomalies of kidney and Ureter. In study, ultrasonography and IVU was done in 50 clinically suspected patients of congenital anomalies of kidney that was admitted in BSMMU, BIRDEM & DMCH during the period of July 2008 to May 2009. Patients of all ages and both sexes were included. Findings of USG and IVU were correlated. Sonographically abnormalities were diagnosed in 46 (92%) cases, out of which 45 (95.7%) also diagnosed by IVU and 1 (33.3) was normal in IVU. Out of 4 (8%) Sonographically demonstrated normal cases, 2 (4.3%) were proved normal by IVU and 2 (66.7%) cases which missed by sonography were diagnosed by IVU. Sensitivity of ultrasonography in diagnosing congenital kidney disease was 95.7% and specificity was 66.7%, positive predictive value was 97.8%, negative predictive value was 50.0% and accuracy was 94.0%. So, we conclude that ultrasonography has significant sensitivity, specificity, positive predictive value, and accuracy in diagnosis of congenital kidney anomalies correlating with IVU. As such, USG can be considered as an appropriate imaging tool for diagnosis of congenital anomalies of kidney.J. Paediatr. Surg. Bangladesh 5(1): 8-11, 2014 (January)